2020
DOI: 10.1093/cid/ciaa034
|View full text |Cite
|
Sign up to set email alerts
|

Single Dose of Doxycycline for the Prevention of Tick-borne Relapsing Fever

Abstract: The current postexposure prophylaxis regimen for tick-borne relapsing fever (TBRF) consists of 5 days’ doxycycline. In this observational study of 77 spelunkers at high risk for TBRF, a single dose of 100 mg doxycycline taken up to 72 hours after exposure to ticks was 100% effective in preventing the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The use of antibiotic medications from 3 months prior to sample collection was recorded in the studied animals since B. persica is sensitive to several antibiotics, possibly leading to negative PCR results, if animals were treated recently [ 10 , 28 , 29 ]. Both the dogs and cats that had received antibiotics close to the time of sampling showed significantly lower seropositivity rates and also lower combined seropositivity or PCR-positivity rates than untreated animals infected with B. persica , probably reflecting the spirochete’s sensitivity to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of antibiotic medications from 3 months prior to sample collection was recorded in the studied animals since B. persica is sensitive to several antibiotics, possibly leading to negative PCR results, if animals were treated recently [ 10 , 28 , 29 ]. Both the dogs and cats that had received antibiotics close to the time of sampling showed significantly lower seropositivity rates and also lower combined seropositivity or PCR-positivity rates than untreated animals infected with B. persica , probably reflecting the spirochete’s sensitivity to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Both the dogs and cats that had received antibiotics close to the time of sampling showed significantly lower seropositivity rates and also lower combined seropositivity or PCR-positivity rates than untreated animals infected with B. persica , probably reflecting the spirochete’s sensitivity to antibiotics. In different studies, it was shown that even one preventive treatment with doxycycline after a tick bite was sufficient to prevent disease in humans [ 29 ] and that the disappearance of spirochetemia in a treated cat was evident 1 day after initial treatment with ciprofloxacin [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on preemptive therapy with a short course of doxycycline (day 1: 200mg/d, day 2-5: 100mg/d) were found to be highly effective in this regard [40,232,233]. A more recent study suggests, that even a single dose of doxycycline is sufficient and as effective [234].…”
Section: Treatmentmentioning
confidence: 99%
“…In summary, multiple clinical trials have demonstrated that single-dose doxycycline for PEP effectively prevents Lyme disease, both in the United States 6 and Europe 12 after a tick bite and prevents at least 2 other spirochetal infections, syphilis 13 and tick-borne relapsing fever caused by Borrelia persica. 14 The updated Lyme disease guidelines explicitly state that the use of PEP does not guarantee the prevention of infection. 2 Clinicians need to provide appropriate education on the signs and symptoms of the infections that may potentially arise following an I. scapularis tick bite, whether due to Lyme disease or another infection potentially transmitted by this tick species, such as babesiosis.…”
Section: Lettermentioning
confidence: 99%